Peran Hak Kekayaan Intelektual dalam Mendorong Inovasi dan Pertumbuhan Bisnis di Indonesia - Annabella Putri Aulia (PT. Hasba Edukasi Mandiri, 2025)
Intellectual Property Rights (IPR) play a strategic role in driving innovation and sustainable business growth in Indonesia. National legal frameworks such as the Patent Law, Copyright Law, and Trademark Law establish a solid foundation to protect creations, inventions, and product identities, thereby ensuring legal certainty for business actors and enhancing national competitiveness. However, challenges such as low legal literacy, slow administrative processes, and weak law enforcement—especially in digital platforms—remain significant obstacles. Optimization strategies for IPR protection should focus on digitalizing services, increasing public awareness, utilizing IPR as collateral for financing, and adapting regulations to emerging digital technologies. Furthermore, cross-sector collaboration among government, businesses, academia, and law enforcement is essential to building a strong innovation ecosystem. With more effective and integrated IPR protection, Indonesia can maximize the economic potential of intellectual assets and foster inclusive and sustainable business growth.